PRECLIINICAL SUB-ACUTE ORAL TOXICITY STUDY FOR ANTI-INFLAMMATORY EVALUATION OF METHANOL EXTRACT OF CUCURBITA PEPO L. SEEDS - SHEHZAD , A; SALEEM , U; GULZAR , F; AHMED , FN; ANWER , R; SHAHAD , M; KOUSAR , S; ZAHID , F; ZAHID , S (Biological and Clinical Sciences Research Journal, 2023)
: Cucurbita pepo, a plant known for its traditional use in managing various ailments, contains valuable phytoconstituents and nutritional components. Aim: This study aimed to assess the sub-acute toxicity of the methanol extract of C. pepo (MECP) seeds according to OECD 407 guidelines. Rats were orally administered MECP at 250, 500, and 1000 mg/kg doses for twenty-eight days. Throughout the study period, the animals were closely monitored for any signs of toxicity, and at the end, blood samples were collected for biochemical and hematological analyses. Histopathological examination was performed on vital organs after euthanizing the rats. The results demonstrated that MECP administration significantly increased body and organ weight in the treated rats. However, food and water intake remained unchanged, and no mortality was observed. Biochemical and hematological analyses revealed no significant changes in the treated groups compared to the control group, except for a notable decrease in red blood cells, suggesting potential anemic effects of MECP. Histopathological examination showed no structural alterations in the liver, heart, and kidney. Based on these findings, it can be concluded that C. pepo is safe for use and holds the potential for therapeutic efficacy.